Socialization mechanisms and goal congruence. (July 2019) - Kennedy, Frances A.; Widener, Sally K.
Abstract: Firms use performance measures linked to incentives and the evaluation process to motivate and direct employees' efforts towards goal congruence. In a research setting where the noise in the performance measures hinders such formal linkage, we examine how firms can achieve goal congruence. We first examine the direct relation between employees' perceptions of the extent to which socialization mechanisms (i.e., perceptions of the extent to which employees perceive that top management communicates core values, supervisors engage in career development mentoring, and employees themselves engage in peer mentoring) are related to goal congruence. Second, we examine the process by which the relationship works. We posit that the relationship works because socialization mechanisms communicate information, which reduces employees' uncertainty thus increasing their perceptions of career security, and in turn, employees become more attached to the firm and better impound its goals. Using survey data from 354 employees to estimate a structural equation model, our results fail to support a direct association between socialization mechanisms and goal congruence. However, we find an indirect association through employees' perceptions of career security. We further find that the indirect effect only holds for non-union employees. Interestingly, for union employees, goal congruence is directly facilitated by employees' perceptions of the extent to which top managers communicate core values.